2022
DOI: 10.5603/cj.a2022.0030
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Murray law-based quantitative flow ratio (μQFR) and three-dimensional quantitative flow ratio (3D-QFR) in non-selected angiographic stenosis: A multicenter study

Abstract: Background The agreement between single-projection Murray-based quantitative flow ratio ( μ QFR) and conventional three-dimensional quantitative flow ratio (3D-QFR) has not been reported hitherto. Methods Patients from a multinational database were randomly selected for the study of agreement, according to sample size calculation. Both conventional 3D-QFR and μ QFR were analyzed for all available arteries at a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Briefly, μQFR, an upgraded technique, is able to compute FFR from a single angiographic view with incorporating Murray bifurcation fractal law. Its diagnostic performance and clinical implications were demonstrated previously 19–22. In the catheterisation laboratory, one single operator will perform angiography-derived FFR measurement.…”
Section: Methods and Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…Briefly, μQFR, an upgraded technique, is able to compute FFR from a single angiographic view with incorporating Murray bifurcation fractal law. Its diagnostic performance and clinical implications were demonstrated previously 19–22. In the catheterisation laboratory, one single operator will perform angiography-derived FFR measurement.…”
Section: Methods and Analysismentioning
confidence: 95%
“…For the angiography-derived FFR-guided strategy arm, an imaging-based FFR (QFR or Murray law-based QFR (μQFR)) will be used, and the criterion for PCI is QFR or μQFR≤0.8 9 19 20. Briefly, μQFR, an upgraded technique, is able to compute FFR from a single angiographic view with incorporating Murray bifurcation fractal law.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…μQFR had a high diagnostic accuracy to estimate FFR even using suboptimal angiographic image projection (13). It was recently shown that single view μQFR had a similar diagnostic accuracy as three-dimensional (3D) QFR (14,15). Thus, μQFR could be used for SB functional assessment.…”
Section: Introductionmentioning
confidence: 99%